Letter from Max Bredig to Marianne and Viktor Homburger, December 25, 1940 - Bredig, Max Albert (1940)
Max Bredig (1902-1977) send Christmas greetings to his sister and brother-in-law, Marianne Homburger (1903-1987) and Viktor Homburger (1888-1968), who are currently interned in the Gurs concentration camp in France. Bredig additionally mentions that he learned of a possibly way for internees to be freed from the camp.
Keywords: Bredig, Max Albert, 1902-1977; Homburger, Marianne, 1903-1986; Homburger, Viktor, 1888-1968; Gurs (Concentration camp)